Overexpression of a LAM Domain Containing RNA-Binding Protein LARP1c Induces Precocious Leaf Senescence in Arabidopsis - Zhang, Bangyue (Korea Society for Molecular and Cellular Biology, 2012)
Leaf senescence is the final stage of leaf life history, and it can be regulated by multiple internal and external cues. La-related proteins (LARPs), which contain a well-conserved La motif (LAM) domain and normally a canonical RNA recognition motif (RRM) or noncanonical RRM-like motif, are widely present in eukaryotes. Six LARP genes (LARP1a-1c and LARP6a-6c) are present in Arabidopsis, but their biological functions have not been studied previously. In this study, we investigated the biological roles of LARP1c from the LARP1 family. Constitutive or inducible overexpression of LARP1c caused premature leaf senescence. Expression levels of several senescence-associated genes and defense-related genes were elevated upon overexpression of LARP1c. The LARP1c null mutant 1c-1 impaired ABA-, SA-, and MeJA-induced leaf senescence in detached leaves. Gene expression profiles of LARP1c showed age-dependent expression in rosette leaves. Taken together, our results suggest LARP1c is involved in regulation of leaf senescence.